Work engagement among generation z in Malaysian private sectors - Lam, Hui Min (2023)
In today’s rapidly changing environment, having an engaged workforce creates a competitive advantage for any organization. Organizations with excellent work engagement reported high growth in earnings compared to those that reported low work engagement levels. In fact, disengaged employees cost an organization as they become less productive. However, having an engaged workforce is considered the most management challenge facing by the organizations. Therefore, this study is conducted with the intention to capture factors that might influence work engagement among generation Z employees. The study examines the direct relationship between work-life balance, social support, rewards, ethical leadership and work engagement. A total of 217 questionnaire were distributed online using Google form through organization’s representative after permission was granted to conduct the study. Response rate was 100%. In this study, hypotheses for direct effect were tested using multiple regression analyses. Results showed that only rewards and ethical leadership was found significantly positively related to work engagement. The findings indicate that work engagement among generation Z employees can be increased if the organization is able to provide with attractive rewards and to have leaders who have high ethical values. Interestingly, social support was found significantly negatively related to work engagement. The findings indicate that work engagement tend to reduce when social support received is high.